1979
DOI: 10.1159/000176257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Raw Field Bean <i>(Vicia faba) </i>on Amino-Acid-Degrading Enzymes in Rats and Chicks

Abstract: The effects of Vicia faba diet on urinary nitrogenous compounds and on enzyme activities of pathways directly associated with amino acid metabolism were studied in rats and chicks. The urea and creatinine excretion of rats fed on V. faba was approximately 90% more than that of control rats. The V.-faba-fed rats had increased activities of liver arginase (EC 3.5.3.1), argininosuccinate synthetase (EC 6.3.4.5) and alanine aminotrans-ferase (EC 2.6.1.2). The chicks fed on V. faba also showed increased activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Care was taken to prepare isoenergetic diets to avoid Using adequate techniques, we reported that the intestinal absorption was diminished in rats on V. faba, which is in reasonable agreement with the elevated values of fecal nitrogen and the decreased urinary nitrogen excretion in these animals [16][17][18].…”
Section: Discussionsupporting
confidence: 78%
“…Care was taken to prepare isoenergetic diets to avoid Using adequate techniques, we reported that the intestinal absorption was diminished in rats on V. faba, which is in reasonable agreement with the elevated values of fecal nitrogen and the decreased urinary nitrogen excretion in these animals [16][17][18].…”
Section: Discussionsupporting
confidence: 78%
“…A significant increase of alanine amino transferase, which helps in the synthesis of glutamate and thus functions as a donor of NH3 group in urea synthesis, aids in the increased catabolism of amino acids [7], A marked increase of aspartate aminotransfer ase also supports this concept, since aspartate is used for urea formation.…”
Section: Discussionmentioning
confidence: 91%
“…23, 27], Many investigators have reported the factors in volved in this phenomenon [1,10,19] and a hypothesis that growth inhibition is largely due to the presence of trypsin or proteinase inhibitors, present in an active form, in raw legumes has been proposed [ 18,24], It has been reported that raw legumes have an influence on the urinary nitrogenous compounds as well as amino acid-degrading enzymes [7]. It has been observed in this lab oratory that green gram (Phaseolus aureus Roxb).…”
Section: Introductionmentioning
confidence: 99%
“…The effects we observed on liver composition suggest that the liver metabolism was affected by the replacement of LA or CA with L-ISO. Previous rat studies using legume-based diets have also reported significant effects on relative liver weights, composition, and enzyme activity [18,[34][35][36] . We hypothesize that differences in protein intestinal absorption may affect the liver protein metabolism which in turn is reflected by tissue composition differences.…”
Section: Discussionmentioning
confidence: 93%